Research on Detection Technology for Breakwater Structures Based on Multi-sensor Information Fusion - LIN Xiaobin; YANG Zhimin (Renmin Zhujiang)
With the rapid development of port facilities,the safety and stability of port wading projects have attracted increasingly more attention in recent years.Under the influences of waves and typhoons on port breakwaters,the abovewater structures of breakwaters are damaged,and the underwater ones are subject to structural fractures,damage,and deformation.To address the problem,this paper proposes a method characterized by data fusion and a principle of multi-sensor integration of unmanned aerial vehicle (UAV) lidar system,SeaBat T50-P multibeam echosounder,GPS RTK,and BV5000-1350 three-dimensional scanning sonar measurement system.A feasibility study of the method is then carried out.The test shows that through data fusion,this method achieves complementary advantages and obtains more detailed and accurate data.The proposed method provides reliable technical support for the detection of port breakwaters and other underwater facilities at ports.